A general observatory control software framework design for existing small and mid-size telescopes. (July 2015) - Ge, Liang; Lu, Xiao-Meng; Jiang, Xiao-Jun
Abstract: A general framework for observatory control software would help to improve the efficiency of observation and operation of telescopes, and would also be advantageous for remote and joint observations. We describe a general framework for observatory control software, which considers principles of flexibility and inheritance to meet the expectations from observers and technical personnel. This framework includes observation scheduling, device control and data storage. The design is based on a finite state machine that controls the whole process.